The Challenge of Politics An Introduction to Political Science - Simon, Douglas W.; Romance, Joseph (CQ Press, 2023)
The Challenge of Politics enables students to see how the subfields of political science converge around a set of crucial questions: can we as citizens and students articulate and defend a view of the good political life and its guiding political values? Can we bring political wisdom to bear on judgments about politics and public issues? Can we develop a science of politics to help us understand significant political phenomena - the empirical realities of politics? Simon and Romance balance the lessons of classic and contemporary theory with contemporary politics and empirical study. The book equips students with the tools they need to explore the impact of philosophy and ideology, to recognize major forms of government, to evaluate empirical findings, and to understand how policy issues directly affect people's lives. This Seventh Edition has been updated content on recent international events throughout.